ВІРТУАЛЬНИЙ КОМПЛЕКС З ПАРАМЕТРИЧНИМ НАЛАГОДЖУВАННЯМ НА ПАРАМЕТРИ ЕЛЕКТРОМЕХАНІЧНОЇ СИСТЕМИ - Чорний, О.П.; Сергієнко, С.А. (Інститут електродинаміки НАН України, Київ, 2019)
An approach to the solution to the problem of the parametric identification of direct and alternating current electromechanical transducers in dynamic modes is presented. The experimental research of the processes of the identification of the parameters of a direct current and an induction motor is described. The efficiency of the developed algorithm for the adjustment to the real electromechanical system of the virtual complex is confirmed, which will enable the solution to the research and diagnostic problems that are not always possible to carry out on the experimental plant. The effectiveness of the algorithm for the determination of the admissibility and specification of the limits of the use of the electromechanical system operation, for the assessment of the operational state of the system and its structural units, for the investigation of the causes of breakages and component damages was proved. References 5, table 1, figures 2.